Faktor risiko yang berhubungan dengan komplikasi Diabetes Mellitus Tipe 2 - Erdaliza, Erdaliza; Mitra, Mitra; Rany, Novita; Harnani, Yessi; Rienarti Abidin, Aldiga (LPPM Hang Tuah Pekanbaru, 2024)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease with an increasing prevalence in Indonesia and globally. Complications from T2DM have serious impacts on the quality of life for patients. The increase in the number of complications in T2DM patients at Selasih Regional Hospital, Pelalawan Regency, is the main issue in this research. The study aims to identify risk factors associated with complications in T2DM patients at Selasih Regional Hospital, Pelalawan Regency. The research design used is a case-control study with a sample of 400 patients (200 cases and 200 controls). Cases are T2DM patients with complications, while controls are T2DM patients without complications. Case and control samples were taken using a systematic random sampling method. Data were collected from the medical records of Selasih Regional Hospital in 2023. Data analysis was conducted using chi-square tests and multiple logistic regression. The results showed that high cholesterol (OR=206.46), duration of DM (OR=79.62), high blood pressure (OR=22.54), and irregular check-ups (OR=4.43) were significantly associated with T2DM complications. Interventions to control cholesterol and blood pressure and to increase routine check-ups can reduce the risk of T2DM complications. Therefore, there is a need for increased education and health promotion programs from the hospital regarding diabetes management to prevent the occurrence of T2DM complications.